GAYA HIDUP HEDONISME MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SAM RATULANGI DI KOTA MANADO - Tambingon, Joulanda; Tasik, Femmy; Purwanto, Antonius (JURNAL ADMINISTRASI PUBLIK, 2016)
The hedonism lifestyle of college students to long-term harm when someone does not want to accept the process and just want results fast and easy, the lack of mutual respect and quality of the nation's leaders are not concerned with morals, dishonest leadership and lack of concern for others. The problems that occur among somestudents of the Faculty of Economics and business of the University of Sam Ratulangi Manado from the pattern of their lives that is overly consumerist behavior in everyday life, the less learning interests, the wrong guidelines impact on free sex, drinks(alcoholic beverages), LGBT, the study is not completed and the completion of the study too long over 5 years. As for the goals of this research is to analyze the lifestyles of hedonism student faculty of Economics and business of the University of Sam Ratulangi in Manado.Research methods used in this research is qualitative research. Informants in this study is 11 students from the Faculty of Economics and business Unsrat in the city of Manado. Data collection is done by observation and interview. The data analyzed in the reduction of the data, the presentation of the data and conclusions/verification.Results of the study prove that female students hedonism lifestyle change when they hang out with new friends in a lecture. When they see their friends who are very mindful of appearances ranging from hair styles, how to dress, bags are in use, shoes that are in use, the assesoris in wearand branded goods are purchased.Popular culture the Manado manners and religious values have a high experienced a shift for the Association and the student mindset i.e. young people who excessively followed the trend of culture outside, free association, the lack of seriousness in learningKey Words: Lifestyle, Hedonism, Student